PENGARUH MEDIA PEMBELAJARAN INTERAKTIF TERHADAP MOTIVASI BELAJAR MATEMATIKA SISWA PADA KURIKULUM MERDEKA - Ramadhan Herianto; Andi Mangaraja; Mariam Nasution (Program Studi Pendidikan Matematika, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Balikpapan, 2026)
This study aimed to determine the effect of PhET-based interactive learning media on students’ motivation in learning mathematics within the implementation of the Merdeka Curriculum. The study employed a quantitative approach using a quasi-experimental method with a pretest-posttest control group design. The population consisted of all eighth-grade students of MTsN 1 Padangsidimpuan, totaling 144 students. The sample comprised 72 students selected through cluster random sampling, with 36 students assigned to the experimental group and 36 students to the control group. The research instruments included a learning motivation questionnaire, a mathematics achievement test, and an observation sheet for students’ learning activities. Data were analyzed using normality tests, homogeneity tests, and an Independent Samples t-test. The results revealed that the average learning motivation score of students in the experimental group increased from 68 to 85, while that of the control group increased from 67 to 72. The t-test results showed a significance value of 0.000 < 0.05, indicating a significant effect of PhET-based interactive learning media on students’ motivation in learning mathematics. Furthermore, the effect size value of 0.85 indicated a large effect. Therefore, PhET-based interactive learning media can be considered an effective tool for enhancing students’ motivation in learning mathematics within the implementation of the Merdeka Curriculum.